Problems Pertaining to Quality Control and Analysis of Electric Power in Networks of 1 kV and Higher and Recommendations on Their Solution - O. G. Shirokov; O. V. Lymarj (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems pertaining to quality control and analysis of electric power in networks of 1 kV and higher. It has been shown that in addition to periodical inspection of voltage transformers it is necessary to make diagnosis of their frequency characteristics. The paper proposes standards on frequency characteristics of voltage transformers and an automated method which has been tested in respect of real objects. The method makes it possible to execute diagnosis of frequency characteristics of voltage transformers directly on site of their operation and simultaneously with an inspection process.